2020
DOI: 10.3390/ma13020412
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Functional Surface Fabricated by Electrically Assisted Micro-Embossing of AZ31 Magnesium Alloy

Abstract: Developing bio-inspired functional surfaces on engineering metals is of extreme importance, involving different industrial sectors, like automotive or aeronautics. In particular, micro-embossing is one of the efficient and large-scale processes for manufacturing bio-inspired textures on metallic surfaces. However, this process faces some problems, such as filling defects and die breakage due to size effect, which restrict this technology for some components. Electrically assisted micro-forming has demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Based on the electroplastic effect in EA microforming, we developed an EA microembossing apparatus for manufacturing typical bioinspired functional surfaces over magnesium alloy AZ31 using a BMG die, and the results indicated that EA microembossing can significantly improve the filling quality of Sharklet patterns. [ 160 ] Meanwhile, EA microforming methods have gradually been used to fabricate other 3D microparts. For example, Mai et al [ 161 ] fabricated microchannels on 316L‐stainless‐steel sheets using EA microembossing, and the results showed that the channels were deeper and the residual stress was smaller when assisted by electricity.…”
Section: Microforming Processes Of 3d Microstructuresmentioning
confidence: 99%
“…Based on the electroplastic effect in EA microforming, we developed an EA microembossing apparatus for manufacturing typical bioinspired functional surfaces over magnesium alloy AZ31 using a BMG die, and the results indicated that EA microembossing can significantly improve the filling quality of Sharklet patterns. [ 160 ] Meanwhile, EA microforming methods have gradually been used to fabricate other 3D microparts. For example, Mai et al [ 161 ] fabricated microchannels on 316L‐stainless‐steel sheets using EA microembossing, and the results showed that the channels were deeper and the residual stress was smaller when assisted by electricity.…”
Section: Microforming Processes Of 3d Microstructuresmentioning
confidence: 99%
“…6 For the production of such surface textures, micromanufacturing processes like laser ablation, micromachining, direct 3D printing, photochemical machining or microcoining can be used. 3 Each process faces specific challenges, which have to be taken into account when selecting the manufacturing strategy. In laser ablation, the spot size has to be quite small for the fabrication of microscopic surface textures.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although direct 3D printing enables the production of complicated textures, the lead times are very high and the selection of materials is limited. 3 Photochemical machining is a costly process in which several process steps and equipment parts are required. 8 Unlike the previously described processes, microcoining provides a method to realize an efficient mass production of textured surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the investigations related to the forming die, investigations regarding the workpiece show influences on the plastic material behavior by an electric current density (electroplastic effect-EPE) [18]. In this context, an increase in plasticity was shown for both long-term [19] and short-term [20] current duration time. This influence is attributed to the movement of free electrons, which lead to an increased (local) temperature of the workpiece due to the Joule heating caused by the electron movement [21].…”
Section: Introductionmentioning
confidence: 99%